Research on Reflection Power Suppression Method of Solid State Amplifier - CHEN Shengyi;LI Xiao;ZHU Junyu;ZHANG Chunlin;LONG Wei;LIU Yang;LIU Shenghua;LU Zhijun (Yuanzineng kexue jishu, 2023)
Solid state amplifier (SSA) has been increasingly applicated in accelerators facilities in recent years. However, with the improvement of the power level, equipment failure caused by reflected power becomes the main risk in long-term operation of SSA. A high-power SSA is usually composed of multiple power amplifier modules through power combiner nets. When the power amplifier modules with unequal amplitudes and SSA operate under a full reflection caused by arcing of the cavity, the modules may be easily damaged due to excessive reflected power. The optimization of the power combiners is an effective means for improving the stability of SSAs under high power reflection. In this paper, the mechanisms and conditions under which reflection power arises were analyzed by using the scattering parameter of the combiner, and the optimization scheme of the combiner to reduce the maximum reflected power was proposed. In addition, a set of 500 MHz 8-way power combiner experimental facility was designed to verify the result of theoretical calculation under various working conditions. Simulation and experimental results show that the reflected power of the power amplifier module not only is related to the matching state of SSA, but also is related to the output state of the power amplifier module itself and parameters of combiner. The total reflected power of the power amplifier module is the sum of the reflected power from the mismatched load and the combined power from the other modules. When all the power amplifier modules of the SSA working perfectly, the reflected power of its own signal of a module is exactly compensated by the sum of the power with opposite phase from all other modules. In this case, the reflected power of the module is only related to the matching state of the SSA, and its maximum value is equivalent to the rated output power of the module. In another case, when one of the SSA’s power amplifier modules is switched off, the reflected power received by some of the modules may be as high as nearly 4 times the rated power of a single module, which will lead to severe overloading of the circulator loads and risk of damage to the modules. Eventually, by optimizing the parameters of the combiner, the maximum reflection power is effectively reduced due to suppress in-phase superposition of the reflected power coupled form other modules. The experimental results are in good agreement with the theoretical calculations, which proves the effectiveness of the optimization scheme. Therefore, this research can provide some valuable references for the subsequent development of higher power SSA for CSNS, SAPS and other accelerator facilities.